Iron Status and Inflammation in Early Stages of Chronic Kidney Disease - Ewelina Łukaszyk; Mateusz Łukaszyk; Ewa Koc-Żórawska; Jolanta Tobolczyk; Anna Bodzenta-Łukaszyk; Jolanta Małyszko (Karger Publishers, 2015)
Background/Aims: One of the most common causes of anemia of chronic disease (ACD) is chronic kidney disease. The main pathomechanism responsible for ACD is subclinical inflammation. The key element involved in iron metabolism is hepcidin, however, studies on new indices of iron status are in progress.The aim of the study was to assess the iron status in patients in early stages of chronic kidney disease, iron correlation with inflammation parameters and novel biomarkers of iron metabolism. Methods: The study included 69 patients. Standard laboratory measurements were used to measure the iron status, complete blood count, fibrinogen, prothrombin index, C-reactive protein concentration (CRP), creatinine, urea, uric acid. Commercially available kits were used to measure high-sensitivity CRP, interleukin 6 (IL-6), hepcidin-25, hemojuvelin, soluble transferrin receptor (sTfR), growth differentiation factor-15 (GDF-15) and zonulin. Results: Absolute iron deficiency was present in 17% of the patients, functional iron deficiency was present in 12% of the patients. Functional iron deficiency was associated with significantly higher serum levels of fibrinogen, ferritin, transferrin saturation, total iron binding capacity, hepcidin and older age relative to patients with absolute iron deficiency. In comparison with patients without iron deficiency, patients with functional iron deficiency were older, with lower prothrombin index, higher fibrinogen, CRP, hsCRP, sTfR, GDF-15, urea and lower eGFR. Hepcidin was predicted by markers of inflammation:ferritin, fibrinogen and IL-6. Conclusion: Inflammation is correlated with iron status. Novel biomarkers of iron metabolism might be useful to distinguish iron deficiency anemia connected with inflammation and absolute iron deficiency.